Contemporary Music Composition “Embryo”| Komposisi Musik Kontemporer “Embrio” - Tri Haryanto; I Gede Ydana (GHURNITA: Jurnal Seni Karawitan, 2021)
The life of living things (humans) is something that begins with various processes and stages of growth and development. Such as the embryonic stage as a living body that is still in the early stages of development (growth), but does not have a clear form yet, it will become something. From this process, the composer turned into an artwork entitled embryo, through gamelan Semar Pagulingan Saih Pitu and Tenganan Selonding style mediums , with a duration of 10-15 minutes. The work of the embryo is divided into 4 (four) parts, each part representing the embryonic phase, each of which has its own characteristics. Genesis which forms the organs of new living things (humans). The growth and development process is divided into several stages, starting from fertilization, that is the meeting of male and female gametes, cell division at the morula and blastula stages, then gastrula forming 3 (three) layers, and finally organogenesis which forms new organs of living things (humans).